2000
DOI: 10.2105/ajph.90.6.947
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplements and physical exercise affecting bone and body composition in frail elderly persons

Abstract: OBJECTIVES: This study determined the effect of enriched foods and all-around physical exercise on bone and body composition in frail elderly persons. METHODS: A 17-week randomized, controlled intervention trial, following a 2 x 2 factorial design--(1) enriched foods, (2) exercise, (3) both, or (4) neither--was performed in 143 frail elderly persons (aged 78.6 +/- 5.6 years). Foods were enriched with multiple micronutrients; exercises focused on skill training, including strength, endurance, coordination, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…First, Tieland et al found that adding a protein and mineral supplementation to an exercise intervention significantly improved appendicular and total muscle mass post-intervention 50. Chin A Paw et al found a significantly improved muscle mass by an exercise intervention combined with a protein, vitamin, and mineral supplementation intervention compared to protein, vitamin, and mineral supplementation 36. Kenny et al found that adding a hormonal dehydroepiandrosterone intervention to an exercise and vitamin and mineral supplementation increased total (but not appendicular) lean mass post-intervention 42.…”
Section: Resultsmentioning
confidence: 99%
“…First, Tieland et al found that adding a protein and mineral supplementation to an exercise intervention significantly improved appendicular and total muscle mass post-intervention 50. Chin A Paw et al found a significantly improved muscle mass by an exercise intervention combined with a protein, vitamin, and mineral supplementation intervention compared to protein, vitamin, and mineral supplementation 36. Kenny et al found that adding a hormonal dehydroepiandrosterone intervention to an exercise and vitamin and mineral supplementation increased total (but not appendicular) lean mass post-intervention 42.…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies met the inclusion criteria for the review; details of these studies are shown in Table 1 . Of these, six studies 19 23 , 27 , 34 , 35 were based in Europe, six were from the USA or Canada, 24 , 26 , 28 , 29 , 36 , 38 , 39 two from South America, 32 , 33 , 37 one from Australia, 30 and two from Japan. 25 , 31 The studies ranged in size from 17 participants 24 to 217 34 , 35 and varied in duration between 8 weeks 26 , 36 and 18 months.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, six studies 19 23 , 27 , 34 , 35 were based in Europe, six were from the USA or Canada, 24 , 26 , 28 , 29 , 36 , 38 , 39 two from South America, 32 , 33 , 37 one from Australia, 30 and two from Japan. 25 , 31 The studies ranged in size from 17 participants 24 to 217 34 , 35 and varied in duration between 8 weeks 26 , 36 and 18 months. 32 , 33 Half of the reviewed studies included two comparison groups (exercise, exercise + nutritional supplement); 19 , 22 24 , 26 , 31 , 36 , 38 , 39 the remaining studies had a factorial design with four groups (exercise, nutritional supplement, both interventions, neither intervention).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations